2014
DOI: 10.4314/njt.v33i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Inception Length of Flow over Stepped Spillway Models

Abstract: ABSTRACT ABSTRACTThis study is the modification of Bauer's development length in order to determine the excess in his length which This study is the modification of Bauer's development length in order to determine the excess in his length which This study is the modification of Bauer's development length in order to determine the excess in his length which This study is the modification of Bauer's development length in order to determine the excess in his length which has not been investigated by earlier resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In the pooled stepped spillway, the mean air concentration is larger than that in the flat stepped spillway. Munta and Otun [25] On increasing the discharge, the length of the non-aerated flow zone and the risk of cavitation both increase. The zone near the inception point is closely related to cavitation damage.…”
Section: LImentioning
confidence: 99%
“…In the pooled stepped spillway, the mean air concentration is larger than that in the flat stepped spillway. Munta and Otun [25] On increasing the discharge, the length of the non-aerated flow zone and the risk of cavitation both increase. The zone near the inception point is closely related to cavitation damage.…”
Section: LImentioning
confidence: 99%
“…2.5 2.5 2.5 2.5 Aeration Aeration Aeration Aeration e e e efficiency fficiency fficiency fficiency e e e equation quation quation quation Aeration performance depends on the initial dissolved oxygen (DO) level, required discharge dissolved , , 1 1 (11) Where La = L -Le is the aerated length; Le is the inception length of [17] given on Table 2, the constants a1, a2, a3, a4 are determined experimentally, Table 3 showed the values of the discharge and the head data, the log of the parameters were plotted on Microsoft excel 2003 (Fig.5) to determine k=0.33 and n=1.5 of Equation (6), which is the flow model employed to run the aeration experiment. For every model, at a given unit discharge and at the standard temperature of 20 o C, the aeration parameters in Equation (11) were determined and plotted, as can be viewed in Figures 6a-8c.…”
Section: Determination Ofmentioning
confidence: 99%
“…From the studies of self aerated spillway flows, [15] concluded that the turbulent boundary layer or development length, caused by the stepped chute, initiated air entrainment when its thickness is approximately the depth of flow. A feasible equation was presented by [16] which overestimated the development length and was modified by [17]; for optimization purpose. This research used the modified inception length of [17] in order to determine the aerated length in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although an unstructured grid needs more time and memory to solve the problem, it is still worth it to use in the study. The unstructured grid for this research was developed in Gambit software by triangular elements [29][30] [31].…”
Section: Geometry and Meshingmentioning
confidence: 99%